Structure and interannual variation of fish communities in the Wailingding marine ranching area of Zhuhai in spring - Yuan, Huarong; Chen, Pimao; Chen, Yuxiang; Zhang, Shouyu (Frontiers in Marine Science, 2024)
The changes in fish community structure hold profound implications for our under-standing of the stability and sustainability of marine ecosystems. To uncover the evolving trends in the fish community structure of the Wailingding marine ranching area, this study analyzed fishery resource survey data collected in April 2020 and March 2023, employed methods such as the relative importance index, Bray–Curtis clustering, similarity percentage (SIMPER) analysis, biomass spectrum, ABC curves, and redundancy analysis to analyze the interannual changes and stability characteristics of fish community structure in spring. The results indicate that 26 and 62 fish species were captured in spring 2020 and 2023, respectively, with Thrissa kammalensis and Leiognathus ruconius merging as the dominant species in each year. In 2020, warm water, upper-middle fish species predominated, followed by a shift to warm water, demersal, and benthic species in 2023. Cluster analysis revealed distinct spatial patterns, with fish communities in both years divisible into three discernible groups. SIMPER analysis identified T. kammalensis in 2020 and L. ruconius in 2023 as the main typical species of the fish communities, with Pampus argenteus and Dasyatis zugei as the primary discriminating species between communities, respectively. The slopes of the standard biomass spectra for both year were less than -1, indicating a decline in the overall biomass of the fish community, particularly among larger-bodied species. ABC curve analysis indicated that the fish community in spring 2020 was in a state of moderate disturbance (W=0.225), while in spring 2023, it was in a state of severe disturbance (W=-0.145). The primary environmental factors influencing fish community distribution in both springs were water temperature, depth, and salinity. In summary, the Wailingding marine ranching area has experienced a transition in dominant fish species towards smaller forage fish species, typified by L. ruconius. The level of disturbance experienced by fish communities is progressively intensifying, leading to a decline in the structural stability. Concurrently, there has been an increase in the biomass of reef-associated and reef-dependent fish species.